Film Studies - Ed Sikov (Columbia University Press, 2009)
Th is book is designed to provide a basic introduction to the academic discipline known as fi lm studies. It covers, in the fi rst eleven chapters, the fundamental elements of formal fi lm analysis, from the expressive content of individual images to the ways in which images link with one another; from the structures of narrative screenplays to the basics of cinematography, special eff ects, and sound. Th e book’s fi nal chapter is a step-by-step guide to writing a fi nal paper for the kind of course for which this textbook has been written. Film Studies is a primer—a pared-down introduction to the fi eld. It is aimed at beginners. It simplifi es things, which is to say that the information it contains is straightforward and aimed at every student who is willing to learn it. It’s complicated material, but only to a point. Th e goal here is not to ask and answer every question, cover every issue and term, and point out the exceptions that accompany every rule. Instead, Film Studies tries to cover the subject of narrative cinema accurately but broadly, precisely but not comprehensively. It is a relatively short book, not a doorstop or makeshift dumbbell. It isn’t meant to cover anything more than the basic elements of formal fi lm studies. Th is book is about feature-length narrative cinema—movies that tell fi ctional stories that last from about ninety minutes to three or three and a half hours. It does not cover documentaries, which are about real people and events. It’s not that documentary fi lmmaking is not worth studying; on the contrary. It’s just that Film Studies is strictly an introduction to narrative cinema. Similarly, there is nothing in Film Studies about avantgarde fi lms—those motion pictures that are radically experimental and noncommercial in nature. Film history is full of great avant-garde works, but that mode of fi lmmaking is not what this book is about.